Cyber-security fortresses built on quicksand. (August 2015) - Smyth, Vincent
Abstract : The recent spate of cyber-security breaches, such as those suffered by Sony, Office and Anthem/BlueCross Blue Shield, underscores just how vulnerable enterprises are to malware and hacker attacks. 1–3 CEOs at organisations of all sizes are well aware of the risks and are taking unprecedented interest in the measures that their IT and security teams are putting into place to fend off potentially catastrophic intrusions into their systems by hackers and other malicious actors. Organisations are building security fortresses to defend against cyber-security threats. But while extremely sophisticated, they are often being built on quicksand. The ability to inventory hardware and software is critical to building a strong cyber-security foundation. But while most organisations have multiple sources of software and hardware inventory data, they usually do not have a means to consolidate that data from across all their systems and environments. This renders the very foundation of their cyber-security fortress vulnerable, explains Vincent Smyth of Flexera Software.